RGS-r, a retinal specific RGS protein, binds an intermediate conformation of transducin and enhances recycling - Chen, Ching-Kang (The National Academy of Sciences of the USA, 1996)
G proteins regulate intracellular signaling by coupling a cycle of guanine nucleotide binding and hydrolysis to transient changes of cellular functions. The mechanisms that control the recycling of transducin, the “pace-setting” G protein that regulates mammalian phototransduction, are unclear. We show that a novel retinal specific RGS-motif protein specifically binds to an intermediate conformation involved in GTP hydrolysis by transducin and accelerates phosphate release and the recycling of transducin. This specific interaction further rationalizes the kinetics of the phototransduction cascade and provides a general hypothesis to explain the mechanism of interaction of RGS proteins with other G proteins.